Mechanical Stability Is Key for Large-Scale Implementation of Photocatalytic Surface-Attached Film Technologies in Water Treatment - Ramos, D.R.; Iazykov, M.; Fernandez, M.I.; Santaballa, J.A.; Canle, M. (Frontiers in Chemical Engineering, 2021)
Replacement of classical tertiary water treatment by chemical-free sunlight-driven photocatalytic units has been proposed. Photocatalysts must be cost-effective, inert, chemically stable, reusable and easy to separate, but also mechanically stable. The effect of mechanical stress on a photoactive TiO2 layer, and on its effectivity for degradation of phenol, as model pollutant has been studied during photocatalytic treatment using NUV-Vis light. Sol-gel (SG) and liquid deposition (LPD) methods have been used to coat spherical glass beads with TiO2. Physicochemical characteristics of coated glass beads were determined by N2 adsorption-desorption isotherms, SEM, EDXS and AFM. Phenol photocatayzed degradation was carried out both in stirred batch and flow reactors irradiated with a medium-pressure Hg-vapour lamp (λ>350 nm). [Phenol] was determined by HPLC, and its photoproducts identified using HPLC/MS. In stirred batch reactor, all LPD-coated glass beads showed higher catalytic activity than SG-coated ones, which increased with calcination temperature. Preliminary etching of the glass beads surface yielded dissimilar results, whereas phenol photodegradation with SG-coated etched glass beads is twice as much as for unetched SG-600 beads, the rate reduces by three fold using LPD etched instead of unetched LPD material. Phenol photodegradation using LPD is similar both in stirred batch and flow reactors. TiO2-coated glass beads exhibited very low photoactivity compared to P25-TiO2 nanoparticles in all cases, though their separation is much easier and almost costless. LPD etched catalyst was recovered and reused in the stirred batch reactor; its activity reduced sharply after the first use, and also lost activity in successive runs, ca. 10 % of activity after each “use & recover” cycle. In the flow reactor, activity loss after the first experiment and recycling (30 %) was much larger than in the following runs, then the activity remained rather constant through several cycles. LPD is more adequate than SG for TiO2 immobilization onto glass beads; their calcination produces relatively strong and reactive photocatalytic films. The durability of the catalytic layer increases using a flow reactor, with the pollutant solution flowing in laminar regime through the photocatalyst bed. Abrasion of the surface is largely reduced and its photoactivity increases.